The role of a “Civic University” in the frame of the Quadruple Helix approach to development:The paradigm of MED-QUAD project - Anna Tozzi (Renewable Energy and Sustainable Development, 2021)
Societies are witnessing profound changes and coping with a great variety of challenges, both foreseen and unexpected, for which are not fully prepared. The transformations at environmental, scientiﬁc, technological, cultural and social level force everyone to rethink the meaning and even the value of the human experience and urge the academic community, policymakers and decision-makers within higher education and wider society to ﬁnd proper solutions.Universities are at the center of this transformation process with their dual responsibilities at local and global scale, coping with the intrinsic difﬁculties in addressing local and global demands to contribute to a more equitable and sustainable society.More and more, higher education sector is required to play as a social agent by exploiting the multiplicity of its knowledges as well as exploring teaching methodologies, curricula and the concept of lifelong learning.Universities must analyse and interpret the current concept of university social engagement and social responsibility and reﬂect on how “glocal” engagement should be included in teaching, learning, research and institutional activities, governance and leadership. They should identify how the different social actors are involved in glocal engagement practices, and how they can interact with them.MED-QUAD project provides an example of university civic engagement in the Mediterranean region, including EU (IT and GR) and non-EU institutions (EG, TN, JO, PA).